Kumarin 8-Hidroksiisokapnolakton-2',3'- Diol dari Daun Micromelum minutum: Aktivitas Sitotoksik dan Efeknya Terhadap Ekspresi Bcl-2 Sel Mieloma= Coumarin 8-Hydroxyisocapnolactone-2'.3'-Diol from Micromelum minutum Leaves - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract Multiple myeloma shows resistance to chemotherapy after being treated for some time, and one of the causes is overexpression of Bcl-2. Several coumarins had been shown to have cytotoxic activity, and one of them, i.e. imperatorin, caused apoptosis on cancer cells by suppressing the expression of Bcl-2. Coumarin 8-hydroxyisocapnolactone-2',3'-diol, isolated from Micromelum minutum leaves, has showed cytotoxic activity on several cancer cell lines. The aims of this study were to find out whether coumarin 8-hydroxyisocapnolactone-2'3'-diol has cytotoxic activity on myeloma cell line and whether the effect was caused through apoptotic process by suppressing the expression of Bcl-2. Cytotoxicity assay was performed on myeloma cell line NS-1, using trypan blue exclusion assay (doxorubicine was used as positive control). Expression of Bcl-2 was examined with immunohistochem-istry method. The result showed that coumarin 8-hydroxyisocapnolactone-2',3'-diol has cytotoxic activity on myeloma cell line NS-1, and the ICj,, were 4.16 ug/ ml (24 hours), 4.22 ug/ml (48 hours), and 2.78 ug/ml (72 hours). The coumarin also suppressed the expression of Bcl-2 with IC~ of 17.88 mg/ml. In conclusion, coumarin 8-hydroxyisocapnolactone-2^3'-diol showed cytotoxic activity on myeloma cell line, and it was achieved by suppressing the expression of Bcl-2.